Design and Implementation of HMI For Monitoring The Imbalance of Current and Voltage Based on Calculation of Maximum Deviation Mean Value Method (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2025)
Voltage and current (V-I) imbalance in a three-phase power system can cause decreased efficiency, increased power losses, equipment heating, induction machine faults, and neutral currents. The main causes of this problem are uneven load distribution, phase failure, or network disturbances. Therefore, monitoring imbalance is critical to determine the right corrective steps. This study aims to design and implement a Human-Machine Interface (HMI) as a tool to monitor voltage and current imbalance using the Calculation Maximum Deviation Mean Value (CMDMV) method. This method calculates the maximum deviation of V-I from each phase to obtain an accurate imbalance value. Current and voltage sensors are used to collect real-time data, which are then processed using CMDMV in the HMI software. The results are displayed in the form of graphs, status indicators, and percentage figures, then compared with a power quality analyzer for accuracy validation. The results show that this HMI system can display V-I imbalance in real-time with a reading error rate when the imbalance condition is below 5%, and when it detects an imbalance in V-I, the indicator turns yellow (WARNING). With the creation of this device, it can help identify V-I imbalances in each phase.